Time Course of Antibiotic and Antifungal Concentrations in Corneal Organ Culture. Issue 1 (January 2016) - Seiler, Theo G.; Tschopp, Markus; Zimmerli, Stefan; Tappeiner, Christoph; Wittwer, Valéry V.; Frueh, Beatrice E.
Abstract : Purpose: Contamination with bacteria and/or fungi is a serious complication in organ-cultured corneas. Hence, antibiotic and antifungal agents are added to the culture medium. The concentration of different antimicrobial and antifungal additives to the media over time has so far not been investigated in detail and is the aim of this study. Methods: Nine human fresh corneoscleral discs were stored in corneal culture medium consisting of 2% fetal bovine serum and minimal essential medium. In addition, the culture medium contained 1200 μg/mL penicillin G, 25 μg/mL amphotericin B, 120 μg/mL streptomycin, and 100 μg/mL voriconazole. The concentration of amphotericin B used was 10 times higher than in clinical routine to facilitate its detection. The cultures were kept at 37°C for 28 days. At days 0, 7, 14, 21, and 28, samples of the culture medium were harvested for analysis of antimicrobial concentrations by liquid chromatography and electrospray ionization tandem mass spectrometry. Results: During corneal storage, the concentration of all antibiotics and antifungal agents declined significantly. By day 28, penicillin G was reduced to 14% of the original concentration. Amphotericin B and streptomycin retained approximately 60% of the original concentration to the end of the experiment and voriconazole maintained stable concentrations after an initial decline to approximately 80% at 7 days. Conclusions: Throughout the entire storage period, the concentrations of penicillin G, streptomycin, and voriconazole exceeded the minimum inhibitory concentrations of all common contaminants, obviating the need for a change of the medium for antimicrobial reasons. Based on the minimum inhibitory concentrations and our findings, the initial concentration of amphotericin B should be raised to 5 μg/mL.